DETERMINATION THE LOADING OF A VESSEL WITH “HEAVY” CARGO ON A VOYAGE UNDER THE TERMS OF A VOYAGE CHARTER PARTY - Koskina, Yuliia; Drozhzhyn, Oleksii; Tykhonina, Iryna (Science-based technologies, 2025)
The paper is focused on determining the procedure for calculating the quantity of cargo that a vessel can take for transportation (voyage loading) in a voyage performed under a voyage charter party. The voyage loading of a vessel with a “heavy” cargo is limited by her cargo carrying capacity on a voyage, which largely depends on the deadweight of the vessel in the climatic zone of the voyage, which is a consequence of the safety requirements for voyage process in accordance with the International Convention on Load Lines. The paper presents a general procedure for calculating the cargo carrying capacity of a vessel, based on different values ​​of the calculated deadweights of the vessel in different climatic zones of the voyage, the procedure for determining which is also presented in the paper. The procedure for determining the calculated deadweights of the vessel as a basis for estimating the voyage loading for voyages with one and two changes in cargo mark is presented. A generalized algorithm for determining the cargo carrying capacity of a vessel is proposed, the implementation of which is illustrated by an examples of the calculations. It is emphasized that the results of calculating the cargo carrying capacity themselves are of an exclusively technological nature, since they only assess the vessel’s ability to accept a certain consignment of cargo for safe transportation by quantity. Currently, the process of a voyage under the terms of a voyage charter party requires the correlation of the obtained calculated the cargo carrying capacity of the vessel for the voyage with the terms on the quantity of cargo. Specified in the voyage charter as a term determined by the charterer, it also in a certain sense limits the shipowner-carrier’s ability to carry a certain uqantity of cargo, establishing the minimum and maximum size of the ship’s consignment. Variants of correlating the estimated cargo carrying capacity of the vessel per voyage with the quantity of cargo in accordance with the voyage charter party are considered, on the basis of which possible variants of the quantity of cargo that will actually be сarryied by the voyage under the terms of the voyage charter party are determined.